(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
To be able to estimate appropriately the fade margin required for an optimum performance of earth-space communication links, some meteorological factors that must be considered includes among others: the annual average of the zero degree isotherm (ZDI) and the rain height. It is desirable to have information about these parameters at specific locations but only the ITU-R recommendation is used right now over Nigeria and the locations where specific information is not available. In this paper, two years of precipitation data (TRMM 2A23) from the Tropical Rain Measuring Mission (TRMM) satellite’s precipitation radar has been analyzed to establish the rain heights over some selected stations in the different geographical regions of Nigeria. The result gotten were compared with recommendation ITU-R P.839 and this showed that the value of rain height quoted by the ITU-R does not reflect the real values over these stations as these parameters are location dependent and so cannot be used to estimate the correct fade margins required for satellite communication. We have also compared the year – to – year variability of the rain height and observed only a slight variability over the two years studied.